1990
DOI: 10.2190/qmr0-jg86-ub6h-93tu
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregnancy on Psychosis: Life Circumstances and Psychiatric Symptoms

Abstract: As part of an ongoing prospective study to correlate mother and infant outcome with social isolation during pregnancy, the Schedule for Affective Disorders, SADS-C, was administered to twenty-seven psychotic patients late in pregnancy. Extensive standardized evaluation of life stresses and social supports included a Prenatal Interview with sixty items relating to demographics, drug use, health and obstetrical history, family involvement and development expectations of the infant, and a thirty-item Difficult Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…Chang and Renshaw reported an amelioration of symptoms during pregnancy (17). Krener and others found that women with schizophrenia received and required less medication to control their thought disorder when they were pregnant (18). W Can J Psychiatry, Vol 47, No 5, June 2002…”
Section: Symptom Variation Across the Menstrual Cycle During Pregnanmentioning
confidence: 99%
“…Chang and Renshaw reported an amelioration of symptoms during pregnancy (17). Krener and others found that women with schizophrenia received and required less medication to control their thought disorder when they were pregnant (18). W Can J Psychiatry, Vol 47, No 5, June 2002…”
Section: Symptom Variation Across the Menstrual Cycle During Pregnanmentioning
confidence: 99%
“…The hypothesis about the protective effects of estrogens is bolstered by the observation that in pregnancy, when estrogen levels are steadily rising, women who have had recurrent acute episodes of schizophrenia do not usually break down (59,60). However, they do suffer postpartum psychoses when estrogen levels have abruptly plummeted (61).…”
mentioning
confidence: 99%
“…A traditional view is that pregnancy may protect against recurrence of major affective disorders or suicide. Recurrences of mania and bipolar depression are not uncommon during pregnancy (18)(19)(20)(21), and lithium has been used safely during pregnancy by many patients (22)(23)(24)(25). Recurrences of mania and bipolar depression are not uncommon during pregnancy (18)(19)(20)(21), and lithium has been used safely during pregnancy by many patients (22)(23)(24)(25).…”
mentioning
confidence: 99%